Soil-water retention capacity of expansive soil improved through enzyme induced carbonate precipitation-eggshell powder - Yunlong Liu; Yanyan Xia; Mudassir Mehmood; Lei Wang; Wen Nie; Yingao Zhao; Zhencai Luo (Biogeotechnics)
Enzyme Induced Carbonate Precipitation (EICP) has been extensively investigated as a promising approach to improve engineering properties of soil, while Eggshell Powder (ESP) is an agricultural waste that effectively fills soil pores. The ESP provides abundant nucleation at sites for the EICP process, further promoting the effective precipitation of calcium carbonate. The research presented in this paper investigated the Soil Water Characteristic Curves (SWCC), permeability coefficient, and microstructure of expansive soil before and after EICP and EICP+ESP modification. A series of laboratory experiments were conducted, including soil water characteristic tests, permeability tests and Scanning Electron Microscopy (SEM). The results proved that the addition of EICP and EICP+ESP into natural expansive soil resulted in a gradual decline in air entry value, residual water content, and permeability coefficient, indicating an increase in water retention capacity and a decrease in permeability. Furthermore, with the intrusion of EICP and EICP+ESP, the contact between particles becomes smoother, and the soil pores become more equally distributed. Ultimately, there was an enhancement in water retention capacity of the natural expansive soil. This study emphasizes the synergistic potential of combining EICP and EICP+ESP as stabilizing additives to enhance the water retention capacity of expansive soil. Moreover, the reuse of ESP provides a sustainable solution for the resource utilization of agricultural waste and the improvement of expansive soil using bio-inspired methods.